(untitled) (Research, Society and Development, 2022)
Pesticides or pesticides are chemical products used to control pests and diseases in plants, aiming to increase productivity and product quality. However, the increase in the frequency of use, application mode, climatic conditions and biotic and abiotic characteristics can define the impact they have on health and the environment. Thus, the objective of the study was to identify the knowledge and perception of rural producers about the risks of using pesticides for health and the environment. To this end, a qualitative-quantitative, descriptive-exploratory research was carried out in the rural area of the municipality of Boa Vista do Buricá - Rio Grande do Sul, in a sample of 91 rural producers. Data were collected through field research using a structured form during the first half of 2021. The analysis of the results was based on descriptive statistical analysis. Rural producers are aware and aware of the risks associated with the use of pesticides, including presenting some symptoms associated with intoxication, such as headache, malaise and nausea, even though they are not clinically diagnosed. They make use of personal protective equipment, but not properly. Studies like this can be important, serving as a basis for guidance for public policies and prevention measures, which should contain training and instructions on the correct and safe use of pesticides, as well as information on their harmful effects on health and the environment.